Development of ASAS quality standards to improve the quality of health and care services for patients with axial spondyloarthritis. Issue 2 (11th October 2019) - Kiltz, Uta; Landewé, Robert B M; van der Heijde, Désirée; Rudwaleit, Martin; Weisman, Michael H; Akkoc, Nurullah; Boonen, Annelies; Brandt, Jan; Carron, Philippe; Dougados, Maxime; Gossec, Laure; Jongkees, Merryn; et al.
Abstract : Objectives: The Assessment of SpondyloArthritis International Society (ASAS) aimed to develop a set of quality standards (QS) to help improve the quality of healthcare provided to adult patients affected by axial spondyloarthritis (axSpA) worldwide. Methods: An ASAS task force developed a set of QS using a stepwise approach. First, key areas for quality improvement were identified, discussed, rated and agreed on. Thereafter, areas were prioritised and statements for the most important key areas were phrased on consensus. Appropriate quality measures were defined to allow quantification of the QS at the community level. Results: The ASAS task force, consisting of 20 rheumatologists, two physiotherapists and two patients, selected and proposed 34 potential key areas for quality improvement which were then commented by 140 ASAS members and patients. Within that process three new key areas came up, which led to a re-evaluation of all 37 key areas by 120 ASAS members and patients. Five key areas were identified as most important to determine quality of care: referral including rapid access, rheumatology assessment, treatment, education/self-management and comorbidities. Finally, nine QS were agreed on and endorsed by the whole ASAS membership. Conclusions: ASAS successfully developed the first set of QS to help improving healthcare for adult patients with axSpA. Even though it may currently not be realistic to achieve the QS in all healthcare systems, they provide high-quality of care framework for patients with axSpA that should be aimed for.